1988
DOI: 10.1093/jac/22.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Once daily administration of netilmicin compared with thrice daily, both in combination with metronidazole, in gangrenous and perforated appendicitis

Abstract: The safety and efficacy of a single daily dose of netilmicin plus metronidazole after appendicectomy for gangrenous and perforated appendicitis was compared with the traditional thrice daily dosage. Twenty patients were enrolled in each group. The antibiotics were given intramuscularly for seven days after operation. Eradication of infection was observed in all patients and the postoperative wound sepsis was the same for each group. A significantly higher peak serum netilmicin level was achieved in the group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…This new approach to aminoglycosides dosing has been explored in preliminary studies with adults. In 1983, Powell et al (26) (13,29,31).…”
mentioning
confidence: 99%
“…This new approach to aminoglycosides dosing has been explored in preliminary studies with adults. In 1983, Powell et al (26) (13,29,31).…”
mentioning
confidence: 99%
“…(As recommended by Jablonski [13], we have used throughout this paper the abbreviations qd and tid to refer to the administration of the daily dose in one administration per day [quoque die] or divided in three equal administrations at 8-h intervals [ter in die].) Preliminary studies have suggested a similar clinical efficacy for aminoglycosides whether given qd, twice daily, or tid (9,18).…”
mentioning
confidence: 99%
“…There have been at least 29 studies in humans, the majority being comparative clinical studies (tables III and IV). Although 22 studies were unable to show any difference in efficacy or toxicity related to the different (20) None Not tested appendixes [86] (metronidazole) Adults with appendicitis and other 114 N q24h (58); q8h (56) None None intra-abdominal infections [87] (metronidazole) Adults with intra-abdominal infections [88] 197 N (tinidazole) q24h (98); q8h (99) Adults with severe bacterial infections [89] a Dosage of aminoglycoside was 9.6 mg/kg for q24h therapy and 4.97 mg/kg for q8h therapy.…”
Section: Human Studiesmentioning
confidence: 99%